Nexus between saving rate and economic growth in developing countries - SEIFU, Minyahel Desta (KDI School, 2015)
This study sought to analyse the nexus between domestic saving and economic growth in developing countries and tried to answer which growth theory (exogenous or endogenous growth theory) upholds. In doing so, the study used both cross sectional and panel data analysis method where, the study uses panel fixed effect model for longitudinal data analysis while OLS and Quantile regression technique is used for cross-sectional dataset from 1980-2013 to analyse the long-run as well as medium to short-run causal relationship between domestic saving rate and economic performance in developing countries. The exogenous growth theory of Solow, stipulate that in the long-run saving rate will have only level effect on economic performance than growth effect. While endogenous theory of growth, articulate higher saving will translate both in to level effect and growth effect at steady-state. The result of regression analysis of the study shows that saving has level effect which is in tandem with both exogenous and endogenous growth theory. Moreover, higher saving also causes increase in economic growth. In summary the empirical result supports the endogenous growth model where domestic saving has both level and growth/rate effect at steady-state in developing countries. The policy implication of the study is that, capital accumulation will have a lasting effect on economic growth and transformation of developing countries through externalities and spill-over effect, knowledge and technological transfer, human capital accumulation etc. higher saving rate leads to increase in income and higher economic growth rate at steady-state.
Thesis(Master) --KDI School:Master of Development Policy,2015